PEMANFAATAN SISTEM PENDUKUNG KEPUTUSAN DALAM PENGELOLAAN DISKON PAKAIAN DISTRO - Muhammad Ardiansyah Sembiring; Mustika Fitri Larasati Sibuea; Rivaldi Rivaldi (Smart Education, 2024)
Abstract: Arif Distro is a business engaged in the sale of distro clothing. So far, what Arif Distro has done to make clothing prices discounted is still looking at how long the item has been sold. It is possible that there are still people interested in the item and there is no need to give a price cut or discount. Based on the problems that have been presented and the explanation, a decision support system is recommended that can help Arif Distro to choose which products to give distro clothing discounts to increase sales. The implementation of this community service utilizes a decision support system with the MOORA (MultiObjective Optimization by Ratio Analysis) method which is a decision-making model that uses a collective approach to its decision-making process. The criteria for the MOORA (MultiObjective Optimization by Ratio Analysis) method at Arif Distro include time (initial purchase), size, color, stock and type of clothing. The purpose of this activity is to be able to apply the MOORA (MultiObjective Optimization by Ratio Analysis) method in determining distro clothing discounts at Arif Distro and to be able to design a decision support system in determining distro clothing discounts at Arif Distro using the PHP programming language and MySQL database.Keywords: SPK; Discount; Distro Clothing Abstrak: Arif Distro merupakan suatu usaha yang bergerak dibidang penjualan pakaian distro. Selama ini yang dilakukan Arif Distro untuk membuat harga pakaian menjadi diskon masih melihat berapa lama barang tersebut laku terjual. Kemungkinan barang tersebut masih ada orang yang minat dan tidak perlu untuk diberikan potongan harga atau diskon. Berdasarkan permasalahan yang telah dipaparkan dan penjelasan tersebut, maka direkomendasikan sebuah sistem pendukung keputusan yang mampu membantu pihak Arif Distro untuk memillih produk mana yang hendak diberikan diskon pakaian distro untuk meningkatkan penjualan. Pelaksanaan pengabdian ini memanfaatkan sistem pendukung keputusan dengan metode MOORA (MultiObjective Optimization by Ratio Analysis) yang merupakan model pengambilan keputusan yang menggunakan pendekatan kolektif dari proses pengambilan keputusannya. Kriteria metode MOORA (MultiObjective Optimization by Ratio Analysis) pada Arif Distro diantaranya waktu (pembelian awal), size (ukuran), warna, stok dan jenis pakaian. Tujuan kegiatan ini adalah dapat menerapkan metode MOORA (MultiObjective Optimization by Ratio Analysis) dalam penentuan diskon pakaian distro di Arif Distro dan dapat merancang sistem pendukung keputusan dalam penentuan diskon pakaian distro di Arif Distro menggunakan bahasa pemrograman PHP dan database MySQL.Kata kunci: SPK; Diskon; Pakaian Distro